Efficacy and sex-specific outcomes after six episodes of percutaneous tibial nerve stimulation treatment on overactive bladder syndrome symptoms - Perez−Martinez, Carlos; Palacios-Galicia, Jose Luis; Vargas-Diaz, Irma B.; Munoz, Alvaro; Cruz, Yolanda (Frontiers in Urology, 2024)
Objective This study aimed to investigate the efficacy of six episodes of percutaneous tibial nerve stimulation (PTNS) treatment for overactive bladder (OAB) symptoms in men and women and to determine the duration of the effects over a 6-month period. Methods Women and men with OAB symptoms participated in the study, which was conducted in accordance with an approved ethical protocol (ISRCTN15733799). Patients underwent six 30-min PTNS sessions, twice per week. The symptoms of OAB were assessed using a voiding diary, the short form of the Overactive Bladder Symptom Score questionnaire (OAB-q SF), and the Patient Perception of Bladder Condition (PPBC), which were self-completed by patients before and after treatment (24 h and at 1, 3, and 6 months). The outcome data were compared for sex and time points using two-way ANOVA for repeated measures. Results PTNS treatment significantly improved the OAB symptoms and quality of life in men and women. PTNS increased the voided volume (p < 0.05) and decreased the frequency of voiding, nocturia, and urgency at 24 h and up to 6 months (p < 0.001). The OABq-SF and PPBC scores were significantly decreased after PTNS (p < 0.001). Urgency was greater in men than in women. The duration of PTNS clinical success on frequency and the perception of improvement in quality of life were greater in women than in men. Conclusion The clinical effects of six sessions of PTNS strongly suggest its potential for shortening, from the standard 12 sessions, to effectively alleviate symptoms of OAB. This therapeutic procedure would reduce both the time and economic costs of OAB treatment.